A Model of Neutralization Techniques. Issue 10 (3rd October 2019) - Kaptein, Muel; van Helvoort, Martien
ABSTRACT: Neutralizations are important explanations for the rise and persistence of deviant behavior. We can find many different and overlapping techniques of neutralizations in the literature, which may be a reason for inconsistent research findings on the use and influence of neutralization techniques. Therefore, by following both a deductive and an inductive approach, this article develops a model that covers these techniques in a logical way. This is a novel approach in studying neutralization techniques. We distinguish four categories of neutralizations: distorting the facts, negating the norm, blaming the circumstances, and hiding behind oneself. Based on a broad inventory of neutralizations that are identified in the literature – something that has not been done before – we operationalized each of the four categories into three techniques, each of which consists of five subtechniques. The resulting model aims to reduce the risk of arbitrariness in the selection of techniques for empirical research and thereby facilitates more consistent future research findings. The model also aims to help better understand how neutralizations work.